ANALISIS LAYOUT PROSES PRODUKSI PADA PERUSAHAAN AIR MINUM DALAM KEMASAN CV. MATAHARI DI KABUPATEN BELU - Fahik, Yohanes Irwanto; Nursiani, Ni Putu; Fanggidae, Ronald P C (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2021)
Layout is an important decision that determines the efficiency of a long-term operation, which will be the basis for determining operating costs, if the decision is not made correctly in determining the layout it can hamper the production process. Besides that, it can lead to waste of costs. CV. Matahari is one of the industries producing drinking water in glass and gallon packaging under the brand MTH. The purpose of this study was to determine the type of layout, effectiveness and efficiency used by CV. Matahari. This study uses the From To Chart method, Activity Relationship Chart and Activity Relationship Diagram. The object observed in this study, namely the production process of bottled drinking water from CV. Matahari. The type of layout used by CV. Matahari is the product layout. The results of the analysis of these three methods were obtained, the distance from the borehole to the finished product is 547 meters with a movement time of 1141 seconds, and the total cost of moving the material is Rp. 2965 after being analyzed so that you get a change in layout with a distance of 542 meters, with a time of 1010.83 seconds, at a cost of Rp. 2642, so as to save costs, shorten distances and save time. Keywords: Layout, From To Chart Method, Activity Relationship Chart and Activity Relationship Diagram